Rancang Bangun WSN Untuk Monitoring Pencemaraan Air Sungai Menggunakan Topologi Mesh Network - Saputra, Yoga Eka; Jusak, Jusak (Journal of Control and Network Systems, 2014)
The quality of water source is important. Rivers in Indonesia are generally extremely heavy polluted by organic wastes from sewage population, and other industries are still many others. Water pollution is a change of state in a water reservoirs such as lakes, rivers, oceans and groundwater due to human activities. Wireless sensor network (WSN) is a wireless network consisting of multiple sensors that work together to monitor physical and environmental conditions such as temperature, water, sound, vibration or earthquake, air pollution and other different places. However, there are shortcomings in the WSN. WSN have limited energy and bandwidth. One way that energy and communication can be more efficient WSN is to organize the network topology. MESH is a line of communication topology in which each node can communicate with each other. Measurement of pH of water with a pH meter analog sensor kits have a percentage of error between 0.37% to 1.86% and water temperature measurements using sensors DS18B20 has an error percentage between 0.606% to 0.73% With these results the system to work well with 98.14% accuracy rate for the pH sensor and 99.27% for the temperature sensor.